PENGARUH KONSELING DENGAN ALAT BANTU PENGAMBILAN KEPUTUSAN (ABPK) TERHADAP KETEPATAN DALAM PENGAMBILAN KEPUTUSAN ALAT KONTRASEPSI PADA MASA NIFAS DI PUSKESMAS RANDUAGUNG KABUPATEN LUMAJANG - Ernawati Ernawati; Nova Hikmawati; Sri Wahyuningsih (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
The implementation of the family planning program in Indonesia has several obstacles, one of which is insufficient counseling, limited data obtained by prospective family planning acceptors, health problems, reserves, access to family planning administration, and lack of spousal/family and regional support. The purpose of this study was to analyze the effect of counseling with ABPK on the accuracy of decision-making for contraceptives during the postpartum period at Randuagung Health Center, Lumajang. This research was a quantitative research withdesign quasi experiment which the plan uses the one group pretest-posttest design. The population of all mothers who gave birth at the Randuagung Health Center in Lumajang in April-May 2023 was 20 people. Respondents were taken by acicdental sampling technique. The results of the Wilcoxon analysis test showed a value of α <0.05, namely (0.000) which means that there is an effect of counseling with ABPK on the accuracy of decision-making for contraceptives during the puerperium at Randuagung health center. It is important to continue efforts to optimize the counseling program with ABPK at the Randuagung health center and other health service centers.